2017
DOI: 10.1038/srep42446
|View full text |Cite
|
Sign up to set email alerts
|

Humans expect generosity

Abstract: Mechanisms supporting human ultra-cooperativeness are very much subject to debate. One psychological feature likely to be relevant is the formation of expectations, particularly about receiving cooperative or generous behavior from others. Without such expectations, social life will be seriously impeded and, in turn, expectations leading to satisfactory interactions can become norms and institutionalize cooperation. In this paper, we assess people’s expectations of generosity in a series of controlled experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 58 publications
6
36
0
Order By: Relevance
“…While small noise does not impact substantially on results (average donation, 〈 d 〉 = 0.37, Gini coefficient of the distribution of donations, G = 0.85) we find that large noise generates a distribution that replicates Engel results in both average and heterogeneity (〈 d 〉 = 0.27; G = 0.71). The results about expectations are close to those found in our earlier experimental work 19 . We will also show that the results are robust against the existence of envious individuals, but they are very much affected by the presence of selfish individuals or free-riders, that never change their expectations and, consequently, their behavior.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…While small noise does not impact substantially on results (average donation, 〈 d 〉 = 0.37, Gini coefficient of the distribution of donations, G = 0.85) we find that large noise generates a distribution that replicates Engel results in both average and heterogeneity (〈 d 〉 = 0.27; G = 0.71). The results about expectations are close to those found in our earlier experimental work 19 . We will also show that the results are robust against the existence of envious individuals, but they are very much affected by the presence of selfish individuals or free-riders, that never change their expectations and, consequently, their behavior.…”
Section: Introductionsupporting
confidence: 92%
“…Expectations in the DG have been recently studied in a series of experiments that allowed to probe the influence of different social factors on the observations 19 . Specifically, we have found that even if we elicit expectations from people in different roles, or from external observers of the social interaction, or from subjects socially distant because they refer to a previous experimental session, or when the money at stake is large, we always find that people expect generous behavior.…”
Section: Introductionmentioning
confidence: 99%
“…16 A Tobit model may be more appropriate for the analysis of the dictators' decision if left-censoring in the dependent variable is a concern. (See [60] or [3] for good discussions of the appropriateness of different models to analyze dictator game decisions.) However, only 7% of the dictators decided to give 0 Euro in our study, which is a very low fraction compared to other studies (A meta-analysis found 36% of dictators to give nothing to the recipient [3], while in a survey-experiment, which also paid only 1 in 10 participants, around 17% of dictators decided to give 0 Euro [59]).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for why people form more uncertain beliefs about the moral character of bad than good agents is a strong prior expectation that people will behave morally 32,33 , thus rendering the bad agent's behavior more surprising. To investigate this possibility, we asked a separate group of participants to predict, in the context of decisions to profit from others' pain, how "most people" would choose (see Supplementary Materials, study 8).…”
Section: Supplementary Table 1)mentioning
confidence: 99%